ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN EKSPOR TEH INDONESIA KE MALAYSIA (2012-2014) - Nur Adlim Yuvina; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia-Malaysia has a long relationship with its dynamic like a roller coaster. Currently the relationship is getting better through economic cooperations. Indonesia can get good access in exporting tea products. This research describes factors relates to tea export economically, socially, and politically. This qualitative research explores varieties of tea products exported to Malaysia as well as the factors beyond. The data are content analysis utilizing books, journals, news form newspapers, twitters, official reports from Indonesia Statistic bureau, and websites. Nation-state level analysis with theory absolute advantage from Adam Smith was used to answer the the question why Indonesia has a very prospective tea export to Malaysia. The result shows Indonesian tea varieties are preferable in terms of cheaper price, better quality, exotic flavor, and the highest catechin/anti-oxidant composition. Good relationship between Indonesia-Malaysia on D-8 to improve agriculture sectors including tea product and Buying Mission are also conducive in increasing the export. Key Words: Export, Tea, Cooperation, Buying Mission Program, Production, Plantation